On the immunotropic effects of a new combined pharmaconutraceutical preparation in osteoarthritis - I. V. Sarvilina; A. M. Lila; O. A. Gromova (Современная ревматология)
Osteoarthritis (OA) is one of the leading causes of disability in the world, but the efficacy and safety of its treatment remain extremely low. This review presents epidemiology of OA, mechanism of its development and modern possibilities of pharmacological regulation of immune-mediated inflammation in OA. We analyze the immunological aspects of oral tolerance phenomenon and the prospects for its use to suppress autoinflammation in OA using combined pharmaconutraceutical preparation Chondroguard® TRIO as an element of nutritional support for patients with this disease. It is emphasized that it is advisable to develop a scientifically based rational approach to the treatment of OA that alleviates symptoms, reduces autoinflammatory affection of articular cartilage and improves its regeneration with the involvement of extracellular matrix components.